Simultaneous Adsorption of Cr(VI) and Phenol from Binary Mixture Using Iron Incorporated Rice Husk: Insight to Multicomponent Equilibrium Isotherm - Ankur Gupta; Chandrajit Balomajumder (International Journal of Chemical Engineering)
Fe modified rice husk was prepared as a low cost biosorbent for the removal of Cr(VI) and phenol both singly and in combination from single and binary simulated synthetic waste water. Rice husk was modified by treating with FeSO4·7H2O. The results showed that impregnation of iron onto the surface of rice husk improved the adsorption capability of both Cr(VI) and phenol. The effects of process parameters for multicomponent system such as pH, adsorbent dose, and contact time onto the percentage removal of both Cr(VI) and phenol were investigated. The experimental data for the adsorption of both Cr(VI) and phenol onto the surface of Fe modified rice husk applied to various kinetic and adsorption isotherm models. Multicomponent isotherm models such as Nonmodified Langmuir, Modified Langmuir, Extended Langmuir, Extended Freundlich, Competitive Nonmodified Redlich Peterson, Competitive Modified Redlich Peterson were applied. The results show that Extended Freundlich model best described the experimental data for both Cr(VI) and phenol from binary solution. Pseudo second-order model agreed well with Cr(VI) while pseudo first-order model agreed well with phenol. Maximum adsorption capacity in synthetic binary solution of Cr(VI) and phenol was found to be 36.3817 mg g−1 for Cr(VI) and 6.569 mg g−1 for phenol, respectively.